UMPSA strengthens strategic ties with 33 industry and community partners - Nor Salwana, Mohammad Idris (UMPSA, 2025)
PEKAN, 10 April 2025 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) continues to strengthen its strategic collaboration network with the signing of memoranda of understanding (MoUs) and memoranda of agreement (MoAs) with 33 collaborative partners from various sectors, held at the Banquet Hall, UMPSA Pekan Campus.